2010
DOI: 10.1177/0044118x10383655
|View full text |Cite
|
Sign up to set email alerts
|

The Lifeworld of Youth in the Information Society

Abstract: Media is now central to how youth form their identities. Media also shapes the cultural background of much of young people’s action and decision making and the institutional framework of social interaction. This article explores this mediated “lifeworld” of young people by examining rates of current media use and the infiltration of media into conventional forms of socialization such as schools, family, and peers. The authors argue that increasing media use coincides with a larger structural shift to an inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
1
15
0
4
Order By: Relevance
“…This is crucial because children and adolescents, compared to older age groups, see modern media as a significant part of their life , where they can meet their cultural and social needs . That means that children and adolescents live a large part of their lives online and, therefore, their lived online experiences are essential to understand how behaviour change interventions should be designed.…”
Section: Discussionmentioning
confidence: 99%
“…This is crucial because children and adolescents, compared to older age groups, see modern media as a significant part of their life , where they can meet their cultural and social needs . That means that children and adolescents live a large part of their lives online and, therefore, their lived online experiences are essential to understand how behaviour change interventions should be designed.…”
Section: Discussionmentioning
confidence: 99%
“…The health literature to date has focused on the negative aspects of social media related to the volume and value of information available for adolescents; 19 the perceived superficial screening of selected information and the possible acceptance of this information that may, of course, be invalid; concerns over the impact of social media on the physical and psychological health of young people, including a sedentary life style, loss of sleep and associated cognitive impairment; and consequences of negative self-perception, bullying, social isolation and reduced social cohesion. 10 More recently this research has focused on the use of social media with adolescent health.…”
Section: Introductionmentioning
confidence: 99%
“…The contemporary popularity of technologically mediated communication is unprecedented-with the Internet becoming a critical player in the development of sexual minority identity formation, self-acceptance, and disclosure (Bond, Hefner, & Drogos, 2009;Morimoto & Friedland, 2011). For example, Bond, Hefner, and Drogos (2009) found that 70% of their gay, lesbian, and bisexual college sample used the Internet to gather sexual orientation information.…”
Section: Introductionmentioning
confidence: 99%